PENGELOLAAN KEUANGAN DESA BINUANG KABUPATEN KAMPAR BERDASARKAN PRINSIP GOOD GOVERNANCE - Nizam, Aidiah Ratna Juita; As’ari, Hasim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Village financial management includes planning, implementation, administration, reporting, and village financial accountability. Regulatively all of these village finances will be documented in the form of APBdes whose management follows various statutory guidelines.This means that the village government is no longer carelessly managing village finances even though the authority is the power of budget users and rests with a village head.Therefore, it is necessary to have good governance in the management of village finances. Good Governance Is proposed to achieve management that is more transparent, accountable and community participatory for all financial users.This research was conducted at the Village Government located in Binuang Village, Bangkinang District, Kampar Regency. This study aims to analyze the financial management of Binuang Village based on the principles of good governance that have not been properly realized.In line with the aims of the researchers above, the research method is qualitative. After the data required in this study are collected, the data is grouped.Then the data were analyzed descriptively, namely analyzing the collected data by describing it completely and realistically as outlined in the form of a table then described in the form of words in detail so that it is easier to understand.The results showed that the financial management of Binuang Village was not well realized in terms of community participatory principles, transparency and accountability. Because there are still several inhibiting factors in village financial management that are not in accordance with the principles of good governance.Â Keywords: Village Financial Management, Good Governance, Transparency, Accountability, Community Participation